Decision making tools for infrastructure project planning - Omar, Mohd. Faizal; Trigunarsyah, Bambang; Wong, Johnny (2008)

(untitled)
Nowadays, most of the infrastructure project developments undertaken are complex in nature, demanding greater skill and technologies, fast track work practices, good decision making and analytical skill, and capabilities to utilize Information Communication Technologies (ICT) specifically in planning phase. During this stage, a lot of vague alternatives were found from strategic to operational level. Therefore, it is desirable to find ways to enhance the efficiency of decision making to avoid such misunderstanding and conflict within organisation or group of people. Further, this paper discusses an overview and applicability of Decision Support System (DSS) tools particularly for project management planning. The main objective of DSS tools is to assist project stakeholders towards better and efficient decision making. Various DSS tools have been developed in the area of construction management in every project life cycle. However, most of the tools were found complicated or it is lack of usability and simplicity. These drawbacks will defeat the purpose of DSS which is to support decision making process. Thus, a framework of DSS environment is proposed to overcome previous shortcomings particularly for project management DSS applications.